2015
DOI: 10.1016/j.snb.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive potentiometric sensor for detection of mercury in Cl−-rich samples

Abstract: a b s t r a c tPotentiometric sensors have been exploited for the determination of Hg 2+ ions. However, applications of such sensors are limited to mercury detection in the absence of a Cl − -rich background since Hg 2+ can readily form coordination complexes with Cl − . This paper describes a potentiometric sensor for the determination of anionic mercury species using tert-butylcalix[4]arene-tetrakis(N,N-dimethylthioacetamide) as anion-selective ionophore and tridodecylmethylammonium chloride as ion exchanger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…While the technical quality of the paper is not very high and the detection limits were likely biased with the 0.1 M Hg­(II) solution used as inner electrolyte, the lifetime and selectivity of the membrane appear to be promising. On the other hand, Qin and co-workers showed that membranes containing the commercially available Lead ionophore IV are responsive to the HgCl 3 – species, allowing its detection in chloride rich media . While this anion is already rather lipophilic, the selectivities were significantly improved relative to those using membranes containing anion-exchanger only, with chloride discriminated against by nearly 9 orders of magnitude.…”
Section: Ionophoresmentioning
confidence: 99%
“…While the technical quality of the paper is not very high and the detection limits were likely biased with the 0.1 M Hg­(II) solution used as inner electrolyte, the lifetime and selectivity of the membrane appear to be promising. On the other hand, Qin and co-workers showed that membranes containing the commercially available Lead ionophore IV are responsive to the HgCl 3 – species, allowing its detection in chloride rich media . While this anion is already rather lipophilic, the selectivities were significantly improved relative to those using membranes containing anion-exchanger only, with chloride discriminated against by nearly 9 orders of magnitude.…”
Section: Ionophoresmentioning
confidence: 99%
“…Nowadays, polymeric membrane ion-selective electrodes (ISEs) have become a powerful analytical tool in a variety of fields [1][2][3][4][5]. Especially in environmental monitoring, such electrodes play an important role in real-time and accurate analysis of some environmental parameters, such as pH, the concentrations of Ca 2+ , NH 4 + , and carbonate [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A rotating silver disk electrode (ATA-1B, Jiangsu Jiangfen Electroanalytical Instrument Co., Ltd., China) with a diameter of 3 mm was used as internal reference electrode as described before to obtain more stable and reproducible potential responses. 36 All experiments were performed with a rotating mode conguration (at 3000 rpm). All electromotive force (EMF) values were measured using a Model CHI 760C electrochemical workstation (Shanghai Chenhua Apparatus Corporation, China) in a Faraday cage in the following galvanic cell: saturated calomel electrode (SCE)/0.1 M LiOAc/sample solution/sensing membrane/inner lling solution/AgCl/Ag.…”
Section: Electrode Preparation and Emf Measurementsmentioning
confidence: 99%